Forest certification management experience in Asia Pacific and Europe: A case study of Malaysia and Sweden - Shah Badri Mohd Nor; Ahmad Fariz Mohamed; Shamsul Khamis (Journal of Forest Science, 2025)
The forest certification is a voluntary programme to ensure that the timber harvested from forests is processed in a sustainable manner by following specific standards. The Programme for the Endorsement of Forest Certification (PEFC) was introduced in 1999 using the bottom-up approach, and it gives flexibility for a country to set up their own PEFC standard based on current practices in sustainable forest management (SFM), regulation, and governance. This practice has led to the development of various PEFC standards for each country; thus, the impact of PEFC certification differs from country to country. In accordance with that, this study aimed to evaluate the PEFC standard application in developed and developing countries, namely in Sweden and Malaysia. The study also analysed the impact of forest certification on governance and economic aspects within Asia Pacific and Europe. The outcome of this study indicates that the PEFC standards developed by these countries showed similarities; for example, both countries are focusing on social and environmental requirements. Meanwhile, the differences were shown in the criteria, terms used, and the focus area. The impact analysis exhibited that countries are facing similar issues, especially market access and premium prices. This study revealed that each country develops different standards based on current practices, forest diversification, and regulations.